2021
DOI: 10.3201/eid2703.204364
|View full text |Cite
|
Sign up to set email alerts
|

Clusters of Drug-Resistant Mycobacterium tuberculosis Detected by Whole-Genome Sequence Analysis of Nationwide Sample, Thailand, 2014–2017

Abstract: Multidrug-resistant tuberculosis (MDR TB), pre-extensively drug-resistant tuberculosis (pre-XDR TB), and extensively drug-resistant tuberculosis (XDR TB) complicate disease control. We analyzed whole-genome sequence data for 579 phenotypically drug-resistant M. tuberculosis isolates (28% of available MDR/pre-XDR and all culturable XDR TB isolates collected in Thailand during 2014–2017). Most isolates were from lineage 2 (n = 482; 83.2%). Cluster analysis revealed that 281/579 isolates (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 32 publications
(29 reference statements)
1
14
2
Order By: Relevance
“…Further study is needed to clarify this issue, especially from a molecular evolutionary perspective. Some studies reported that lineage 2 has higher transmissibility than lineage 4 ( 19 , 20 ). However, the present study found no association between the genotype and clustering rates of RR-TB strains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further study is needed to clarify this issue, especially from a molecular evolutionary perspective. Some studies reported that lineage 2 has higher transmissibility than lineage 4 ( 19 , 20 ). However, the present study found no association between the genotype and clustering rates of RR-TB strains.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found 75.0% of isolates within a cluster were collected from the same county, indicating that the recent transmission mainly occurred in local area. In some clusters, isolates exhibited different drug-resistant types in relation to chronology, suggesting the progression and accumulation of mutations linked to drug resistance ( 19 ). Interestingly, some clusters included isolates of different drug-resistant types and ancestral isolates carried more drug-resistant mutations than their descendants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few studies of MDR M. tuberculosis based on whole-genome sequencing at the nationwide scale in Asian countries ( 10 , 11 ). MDR M. tuberculosis belonging to lineage 2 caused an ongoing MDR M. tuberculosis epidemic throughout Central Asia ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…MDR M. tuberculosis belonging to lineage 2 caused an ongoing MDR M. tuberculosis epidemic throughout Central Asia ( 10 ). Of drug-resistant M. tuberculosis isolates, 83.2% belonged to lineage 2 in Thailand, and clusters of these isolates contributed to the high prevalence of drug-resistant TB in that country ( 11 ). Those results are consistent with the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%